Beliefs and Characteristics Associated With Believing Nicotine Causes Cancer: A Descriptive Analysis to Inform Corrective Message Content and Priority Audiences. Issue 8 (6th April 2022) - Weiger, Caitlin; Moran, Meghan Bridgid; Kennedy, Ryan David; Limaye, Rupali; Cohen, Joanna
Abstract: Introduction: Many cigarette smokers want to quit but have not. Switching to noncombustible products can reduce disease risk, but misperceptions that nicotine causes cancer might impact relative harm perceptions about noncombustible products and considering switching. Identifying which smokers are most likely to hold this misperception and associated beliefs can inform the content of and priority audiences for corrective messaging. Methods: Bivariable log binomial models were run on a sample of 9, 013 adult established smokers from Wave 3 of the Population Assessment of Tobacco and Health. Post hoc testing identified groups and beliefs associated with significantly higher-than-average prevalence of the misperception. Results: About 61.2% of smokers believe nicotine causes cancer or don't know. Non-Hispanic Black (PR: 2.09) and Hispanic (PR: 1.73) smokers, as well as those making under $10, 000 a year (PR: 1.36) had significantly higher-than-average prevalence of the misperception. Smokers who had recently used ENDS or smokeless tobacco had significantly lower-than-average prevalence of the misperception (PR: 0.70 and 0.63, respectively). Prevalence of nicotine misperceptions was significantly higher-than-average among those who recognized all ten smoking-caused diseases (PR: 1.34), believed additive-free cigarettes were more harmful than regular cigarettes (PR: 1.71), or did not report subjective norms supporting noncombustible use (PR: 1.05). Conclusion: High perceived threat of tobacco may be overgeneralized to nicotine. High prevalence of the misperception among Non-Hispanic Black and low-income smokers is concerning, considering existing health disparities. Messaging should attempt to correct the misperception that nicotine causes cancer. Inferential reasoning after message exposure should assess accuracy of relative harm perceptions. Implications: The current study supports the need for corrective messaging to address the misperception that nicotine causes cancer. Identifying that nicotine misperceptions are associated with higher harm perceptions about tobacco suggests that there may be unintended consequences of high perceived harm of tobacco that need to be addressed. As nicotine misperceptions are significantly more prevalent among those already at higher risk of tobacco caused diseases, care should be taken to ensure equity in message dissemination.